Biarticular Rigid Powered Lower Extremity Exoskeleton Robot - Chen, Tianchi; Liu, Zhi; Li, Chaoyang; Chen, Xiaoan; Hu, Jianjun; Wu, Jiaxun; He, Ye (IEEE robotics and automation letters, 2025)
Lower extremity exoskeletons designed for multi-joint assistance are increasingly explored for rehabilitation and human augmentation. However, conventional monoarticular designs often suffer from joint misalignment and actuator redundancy, limiting their efficiency and user comfort. This study presents a biarticular rigid powered lower extremity exoskeleton that simultaneously assists the knee and ankle joints through a single actuator, enabling coordinated torque generation across adjacent joints. A hierarchical control framework combining gait segmentation, impedance-based torque generation, and gravity/friction compensation is implemented to provide phase-specific assistance. Experimental results show that the proposed exoskeleton reduces gastrocnemius activation by up to 63.4% and metabolic cost by up to 11.6% during stair ascent, with corresponding reductions of 28.3% and 8.2% during level walking. These findings demonstrate the effectiveness of the biarticular and underactuated structure in enhancing locomotor efficiency, highlighting its potential as a compact and practical solution for dynamic and diverse mobility scenarios.